Assessing the Need for Establishing Land, Soil, and Crop Information Hubs to Support Climate-Smart Agriculture in Ethiopia, Kenya, and Rwanda - Recha, John W.M.; Kooiman, Andre; Gitau, Angela; Snel, Herman; Weert, Frank van; Woude, Thaisa van der; Genova, Giulio; Okoti, Michael; Okwuosa, Elizabeth; Were, Kennedy; Diga, Girma M; Abera, Dejene; et al. (Land, Soil and Crop Information Services to Support Climate-Smart Agriculture in Eastern Africa (LSC-IS), 2025)
The Land, Soil, and Crop Information Services (LSC-IS) to support Climate-Smart Agriculture project (2021-2025) aims to establish sustainable data hubs within national agricultural research organisations in Ethiopia, Kenya, and Rwanda.